VD_FINDINFO HC / 2011 / 105 vom 13. Januar 2011 - VD Tribunal cantonal (2011)
ENFANT, OBLIGATION D'ENTRETIEN, REVENU HYPOTHÉTIQUE, DÉPENS | 145 al. 1 CC, 280 al. 2 CC, 285 al. 1 CC, 452 al. 1ter CPC, 92 al. 2 CPC